Hydrotreatment of renewable oils using hierarchical mesoporous H-ZSM-5 synthesized from kaolin clay1. Issue 49 (30th May 2015) - Kumar, Rohit; Rana, Bharat S.; Verma, Deepak; Rayaroth, Swaroop; Prasad, V. S.; Sinha, Anil K.
<x xml:space="preserve">Abstract</x> Hierarchical mesoporous ZSM-5 with tailored physicochemical properties was successfully synthesized by using kaolin clay as a cheap alumina source and organosilane as a mesopore directing agent.